The Influence of Work Culture on Employee Commitment With the Work Environment as a Moderation Variable At the Binjai City Regional Secretariat Office - Eva Herdalina Pardede; Mesra B (International Journal of Society and Law, 2024)
A work culture that is not clearly understood and a low level of employee commitment will cause inconsistency in behavior and lack of motivation of employees at work. The purpose of this study is to find out and analyze the role of the work environment in strengthening the influence of work culture on employee commitment at the Binjai City regional secretariat office. This research was conducted with a causal associative quantitative approach. The sample used was all ASN employees with a total of 82 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) showed that: 1) Work culture had a positive and significant effect on work commitment with a T-statistic value of 25.026 > 1.96 and a P-Value of 0.000 < 0.05; 2) The work environment has a positive and significant effect on work commitment with a T-statistic value of 4.164 > 1.96 and a P-Value of 0.000 < 0.05; and 3) the work environment was not able to significantly strengthen the influence of work culture on work commitment with a T-Statistic value of 0.791 < 1.96 with a P-Value of 0.431 > 0.05. These findings confirm that in the context of this study, the work environment does not have a significant impact in strengthening the relationship between work culture and employee work commitment. This shows that while a conducive work environment is important in improving employee satisfaction and well-being, when it comes to work commitment, other factors also need to be considered. Rewrite neatly without diminishing meaning